Integrated Paired Literacy Model Problem-Based Learning to Improve Biology Learning Outcomes - Faradila, Anisa; Prafitasari, Aulya Nanda; Farida, Amaliyah (Universitas Islam Negeri Walisongo Semarang, 2023)
The application of PBL learning can improve students' literacy skills because the learning activities require students to actively engage in literacy to find solutions to a given problem. Literacy skills are very important for students to have in learning biology; through these skills, students can improve their learning outcomes. Health literacy skills to support student learning outcomes are supported by the application of paired literacy techniques. Through the Classroom Action Research (CAR) method with a cyclical research model over 5 weeks, it is expected to be able to improve the learning outcomes of class XI Science. Data collection was carried out by testing techniques with quantitative data types. Therefore, it can be concluded that paired literacy activities in the PBL model can improve biology learning outcomes in the reproductive system material of class XI Science students with a classical completion percentage of 61.11%.